Indicators of economic assessment of an industrial enterprise - Ponomarov, V. D. (Teadmus OÜ, Tallinn, 2025)
In addition, it is stated that the indicators of economic evaluation of industrial enterprises are not only a tool for diagnosing the current state of business, but also the most important element of strategic management. Competent use of these indicators contributes to increasing the efficiency of the enterprise, its financial stability and competitiveness valuation models that take into account the rapidly changing conditions of the modern economy.
Keywords: economic evaluation; efficiency; industrial enterprises; evaluation; indicators